Divirta-se quem puder: história e lazer em Belo Horizonte através da revista Semana Illustrada, 1927-1928 - Andreza Gonsalez Rodrigues Mota (2018)
This paper focuses on the research and analysis of the leisure portrayed by Semana Illustrada magazine, mainly based on the publications distributed in the state of Minas Gerais, Brazil, between the years of 1927 and 1928, currently stored in the Historical Newspaper Library's collection of the State Public Library Luiz de Bessa (Belo Horizonte, MG). One of the main features of the magazine, which distinguished it from the competition at the time, was the ability to publish self-explanatory images; that is, they did not require auxiliary texts to be understood. Despite of its short lifespan, "Semana Ilustrada" ("Illustrated Week") used to publish content about the appropriation of public spaces by the most wealthy layers of Minas Gerais society, such as mass, jogging (written as footing at the time), picnicking, sports (written as sportes at the time), as well as articles of artistic, humorous, critical, literary and also news format. In addition, the magazine made a point of honoring the various members of the high society when they show up in private spaces created specifically for the elite meeting, such as the Cassino Capitólio and the Theatro Municipal; movie theaters like Glória, Avenida and Pathé, without missing some pubs like "Stadt Wien", "Grande Hotel" and "Império". But the almost complete omission of conflicts brought about by urbanization was represented in its continuous content, although criticism is characteristic of its definition in its working hours and present in some covers, chronicles, verses and illustrations. Being one of the newspaper's important characteristics, its commercial character evidenced its concern with the formation of a consumer market. Finally, in general it was noted that, in summary, there is a great indication that the great target audience of "Illustrated Week" was composed of young students and adults, being the consumers of the sophisticated products and the new habits of modernity published in the journal, including amusements. After all, the average, literate and more fortunate layers that occupied the spaces in the magazine, with the justification and effort of the newspaper to show that only the same occupied the spaces of the city.